Nivolumab-induced hepatitis: A rare side effect of an immune check point inhibitor. (March 2020) - Mathew Thomas, Vinay; Bindal, Poorva; Ann Alexander, Swetha; McDonald, Kymberly
Immune checkpoint inhibitors have ushered in a new era in cancer management. Nivolumab is a human immunoglobulin G4 (IgG4) monoclonal antibody that selectively inhibits programmed cell death-1 (PD-1) activity by binding to the PD-1 receptor. This inhibits suppression of the T-cell activity, which can in turn cause increased killing of cancer cells. This alteration in the activity of the T cells can cause them to lose their ability to identify host cells and leads to immune-related adverse effects (irAE). Nivolumab-induced hepatotoxicity is rare and accounts for 3–6% of all irAE. We present a case of nivolumab-induced hepatitis. A woman who was treated for recurrent renal cell carcinoma presented with hepatitis. Workup for other causes was negative and the hepatitis was attributed to the administration of nivolumab. She was started on oral steroids followed which she initially improved. However, she later presented with massive upper gastrointestinal bleeding secondary to gastroduodenal ulcers and subsequently developed acute tubular necrosis and passed from the complications. Immune checkpoint inhibitors have proven to be a promising approach in the management of a wide array of neoplasms by immunomodulation. As these agents are becoming standard of therapy in the management of cancers, a heightened vigilance in the diagnosis of irAE is warranted. With heightened vigilance, early recognition can lead to decreased mortality and morbidity.